A novel human ex-vivo burn model and the local cooling effect of a bacterial nanocellulose-based wound dressing. Issue 8 (December 2020) - Holzer, Judith C.J.; Tiffner, Katrin; Kainz, Sonja; Reisenegger, Peter; Bernardelli de Mattos, Ives; Funk, Martin; Lemarchand, Thomas; Laaff, Helmut; Bal, Ayse; Birngruber, Thomas; Kotzbeck, Petra; Kamolz, Lars-Peter
Highlights: Wound dressings made of BNC significantly reduce intradermal temperature after burn injuries. The cooling effect is based on evaporation. Histology showed less thermal damage of epidermis and dermis after burn injuries that received cooling treatment. Immunofluorescence showed more viable cells in the burn injuries that received cooling treatment. Abstract: Background: Burn wound progression is a significant problem as burns initially thought to be superficial can actually become full thickness over time. Cooling is an efficient method to reduce burn wound conversion. However, if the cooling agent is below room temperature, depending on the wound size the patient is at risk of hypothermia. Additionally, tissue perfusion is reduced leading to an aggravation of burn wound progression. We investigated if wound dressings based on non-pre-cooled bacterial nanocellulose (BNC) with a high water content cool a burn just by evaporation and reduce the intradermal damages in the skin. Material and methods: In a human ex-vivo model, skin explants underwent contact burns using a 100 °C hot steel block. The burned areas were divided into two groups of which one was cooled with a BNC-based wound dressing. Intradermal temperature probes measured temperature in cooled and uncooled burn sites over 24 h. For histological assessments of the burned areas biopsies were taken at different time points. High mobility group box-1 (HMBG1) staining served as marker for cell vitality and necrosis in the different skin layers. Results: Intradermal temperature measurement showed that application of the BNC-based wound dressing reduced temperature significantly in burned skin. This cooling effect resulted in a maximum temperature difference of 6.4 ± 1.9 °C and a significant mean reduction of the area under the curve in the first hour after burn of 62% (p < 0.0001). The histological results showed less necrosis and less dermal-epidermal separation in the cooled areas. The HMGB1 staining revealed more vital cells in the cooled group than in the uncooled group. Conclusion: Based on our results, BNC-based wound dressings cool a burn. Intradermal temperature as well as thermal damage of the tissue was reduced. The tested BNC-based wound dressing can be used without pre-cooling to cool a burn as well as to reduce the burn BNC-based wound progression through its evaporation cooling effect.